Pengembangan Sistem Informasi Point Of Sale Pada Toko King’s Sports - Septa, Muhamad Septa Pebriawan (Sekolah Tinggi Ilmu Komputer El Rahma, 2025)
The development of information technology has grown very rapidly following the needs of the times that require speed and accuracy in all aspects of life. Development follows in terms of hardware, software, as well as in terms of human resources that operate it. At this time, almost all areas of life require information technology and human behavior is accustomed to applying information technology in everyday life. With computers we can perform data processing and data storage. Can also input data, edit data, save, delete, etc. So that data is managed more effectively and efficiently. With today's rapid technological advances, an idea or ideas from the author has emerged to try to computerize data collection and sales transactions in a business entity. The author tries to build an application that will help to simplify data processing and sales transactions. With the aim of simplifying data processing to be more optimal and effective. The program that will be made is